THE INFLUENCE OF MODERN REQUIREMENTS ON THE TEACHING OF CHEMICAL DISCIPLINES BY MASTERS OF PHARMACY - Филиппова, Лариса (SWorldJournal, 2021)
The article considers how trends in the development of the pharmaceutical industry affect the professionally oriented study of chemical disciplines by future masters of pharmacy. We will analyze the principles and approaches on which the theoretical found